Dosage compensation via transposable element mediated rewiring of a regulatory network. - Ellison, C.E.; Bachtrog, D. (Science, 2013)
Transposable elements (TEs) may contribute to evolutionary innovations through the rewiring of networks by supplying ready-to-use cis regulatory elements. Genes on the Drosophila X chromosome are coordinately regulated by the male specific lethal (MSL) complex to achieve dosage compensation in males. We show that the acquisition of dozens of MSL binding sites on evolutionarily new X chromosomes was facilitated by the independent co-option of a mutant helitron TE that attracts the MSL complex (TE domestication). The recently formed neo-X recruits helitrons that provide dozens of functional, but suboptimal, MSL binding sites, whereas the older XR chromosome has ceased acquisition and appears to have fine-tuned the binding affinities of more ancient elements for the MSL complex. Thus, TE-mediated rewiring of regulatory networks through domestication and amplification may be followed by fine-tuning of the cis-regulatory element supplied by the TE and erosion of nonfunctional regions.